A Paradigm Shift in Primary Open Angle Glaucoma - Eltis, Mark (Canadian Journal of Optometry, 2012)
The definition, diagnosis and management of glaucoma have changed radically over the last decade. This paper reviews recent advances in primary open angle glaucoma and how they were applied to the case of a 68-year-old patient.